EURECA - THE FUTURE OF CRYOGENIC DARK MATTER DETECTION IN EUROPE - Kraus, H; Armengaud, E; Bauer, M; Bavykina, I; Benoit, A; Bento, A; Bluemer, J; Bornschein, L; Broniatowski, A; Burghart, G; Camus, P; Chantelauze, A; et al. (2009)
EURECA (European Underground Rare Event Calorimeter Array) is an astro-particle physics facility aiming to directly detect galactic dark matter. The Laboratoire Souterrain de Modane has been selected as host laboratory. The EURECA collaboration unites CRESST, EDELWEISS and the Spanish-French experiment ROSEBUD, thus concentrating and focussing effort on cryogenic detector research in Europe into a single facility. EURECA will use a target mass of up to one ton, enough to explore WIMP - nucleon scalar scattering cross sections in the region of 10-9 - 10-10 picobarn. A major advantage of EURECA is the planned use of more than just one target material (multi target experiment for WIMP identification). © EAS, EDP Sciences 2009.